The public library : a photographic essay - Dawson, Robert, 1950- (Princeton Architectural Press, 2014)
"Many of us have vivid recollections of childhood visits to the public library: the unmistakable, slightly musty scent, the excitement of checking out a stack of newly-discovered books. Today's libraries also function as de facto community centers, and offer free access to the Internet, job-hunting assistance, or a warm place to take shelter along with the endless possibilities that spark your imagination the moment you open the cover of a book. There are more than 17,000 public libraries in America. Over the last eighteen years, photographer Robert Dawson has traveled the nation, documenting hundreds of these institutions--from Alaska to Florida, New England to the West Coast. The Public Library presents a wide selection of Dawson's photographs, revealing a vibrant, essential, yet seriously threatened system. Essays, letters, and poetry by a collection of America's most celebrated writers--including E. B. White, Isaac Asimov, Anne Lamott, Amy Tan, Charles Simic, Dr. Seuss, and Philip Levine, as well as the voices of dedicated librarians working today--are woven with photographs of the majestic reading room at the New York Public Library; the one-room Tulare County Free Library built by former slaves, in Allensworth, California; the architectural wonder of Seattle's glass and steel Central Library; and the Berkeley, California tool lending library; among many others. A foreword by Bill Moyers and an afterword by Ann Patchett bookend this important survey of a treasured American institution"--